Health of Convicted Persons in the Third Generation of the Longitudinal Cambridge Study in Delinquent Development - Skinner, Guy C. M. (International journal of offender therapy and comparative criminology, 2023)
Research suggests that convicted persons are more likely than non-convicted persons to suffer poor health. However, few longitudinal studies have investigated associations between health and offending across generations. Using the Cambridge Study in Delinquent Development, this article prospectively investigates the relationship between health and offending across generations and between genders. At the average age of 25, third generation convicted males and females reported a higher incidence of serious drug use than non-convicted persons. Convicted males reported a higher incidence of mental illness and self-harm, whereas convicted females reported a lower incidence of physical illness, mental illness, self-harm and hospitalizations when compared to non-convicted females. Convicted males reported a higher incidence of industrial accidents, sports injuries and fight injuries, but a lower incidence of road accidents, whereas convicted females were more likely to report road accidents. Like their fathers, convicted males show worse health compared to non-convicted individuals.